The International Monetary Fund in the system of the international economic organizations - Фіннік, С. Г. (Theory and practice of jurisprudence, 2016)
The factors of creation and role of international economic organizations, and also place of IMF, are examined in their classification in the article. The main role of IMF is underlined in the system of the international economic organizations.